Implementasi Konsep Setara pada Ruang Luar Fasilitas Layanan Disabilitas Fisik di Denpasar: Indonesia - Nyoman Maha Ayuning Tri Cahaya Pringgadani; Agus Kurniawan; Gde Bagus Andhika Wicaksana; I Gede Surya Darmawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
Outdoor spaces for persons with physical disabilities are often designed merely to satisfy minimum accessibility standards, without providing opportunities for participation or equal spatial experience. Meanwhile, Denpasar records 623 individuals with physical disabilities who require inclusive and sustainable rehabilitation facilities. This study aims to identify and implement the concept of equality in the design of outdoor areas for disability service facilities in Denpasar as a foundation for creating an inclusive and equitable environment. The research adopts a descriptive qualitative approach through literature review, site observation, and comparative study of disability service facilities. The findings indicate that the implementation of the equality concept can be realized through three key aspects: equal access and movement provided by a single circulation route accessible for wheelchairs, equal activity and independence facilitated by hydroponic gardens and therapeutic pools that can be used without assistance, and equal social relations supported by communal activity spaces that encourage interaction between disabled and non-disabled users. These results demonstrate that the equality concept can serve as a humanistic design approach for outdoor spaces, enhancing independence and social engagement among people with physical disabilities.